2020
DOI: 10.1099/ijsem.0.004265
|View full text |Cite
|
Sign up to set email alerts
|

Dickeya oryzae sp. nov., isolated from the roots of rice

Abstract: A novel Gram-stain-negative strain, designated ZYY5T, was isolated from rice roots. Results of 16S rRNA gene analysis indicated that strain ZYY5T was a member of the genus Dickeya , with a highest similarity to Dickeya zeae DSM 18068T (98.5%). The major fatty acids were summed feature 3 (C16:1 ω7c and/or C16:1 ω6c), C16:0 and summed featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 40 publications
3
61
1
Order By: Relevance
“…High genome dissimilarity was observed among the D. zeae species complex with a dDDH value of 56-68.20 %, which is lower than the recommended cut-off value (70%) (Wayne et al, 1987;Goris et al, 2007). Additionally, the ANI value within the D. zeae species was 94.33-96.27%, which overlaps the threshold value (ANI 95-96%) (Richter et al, 2009;Goris et al, 2007;Kim et al, 2014;Chun et al, 2018;Wang et al 2020 Figure S1). The dDDH phylogenetic tree was inferred with FastME 2.1.6.1 from GBDP distances calculated from genome sequences (Meier-Kolthoff et al 2013).…”
Section: Comparative Genomics and Phylogenomic Analyses Within Dickeymentioning
confidence: 82%
See 2 more Smart Citations
“…High genome dissimilarity was observed among the D. zeae species complex with a dDDH value of 56-68.20 %, which is lower than the recommended cut-off value (70%) (Wayne et al, 1987;Goris et al, 2007). Additionally, the ANI value within the D. zeae species was 94.33-96.27%, which overlaps the threshold value (ANI 95-96%) (Richter et al, 2009;Goris et al, 2007;Kim et al, 2014;Chun et al, 2018;Wang et al 2020 Figure S1). The dDDH phylogenetic tree was inferred with FastME 2.1.6.1 from GBDP distances calculated from genome sequences (Meier-Kolthoff et al 2013).…”
Section: Comparative Genomics and Phylogenomic Analyses Within Dickeymentioning
confidence: 82%
“…was reclassified as D. oryzae (Wang et al, 2020), a novel species within genus Dickeya. However, we included the genome of EC1 in our analyses because of the close relationships with D. zeae strains.…”
Section: Genome Comparisons Of Dickeya Zeae Species Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…Pairwise isDDH analysis ( S5 Fig) found that these previously identified strains from rice reached the cut-off (90.00%) for a subspecies [43], and they were also suggested to be a subspecies within D. zeae [15].On other hand, ANI and AP analyses suggested EC2 was also close to the other two strains from non-rice hosts, NCPPB 3531 and CSL_RW192 (S5 Fig). In accordance with this, strains EC1, ZJU1202, DZ2Q, NCPPB 3531, and CSL RW192, were classified into a genomospecies named D. oryzae [44]. However, most of the genome sequences used in ANI and AP analyses were draft genomes, and ANI and AP analyses were based on pairwise comparisons.…”
Section: Zeae Strain Ec2 Was Closest To Previously Identified Stramentioning
confidence: 87%
“…In accordance with this, strains EC1, ZJU1202, DZ2Q, NCPPB 3531, and CSL RW192, were classified into a genomospecies named D . oryzae [ 44 ]. However, most of the genome sequences used in ANI and AP analyses were draft genomes, and ANI and AP analyses were based on pairwise comparisons.…”
Section: Discussionmentioning
confidence: 99%